MELIHAT WAJAH ISLAM DARI ORIENTALIS: TELAAH NALAR ORIENTALIS TENTANG HUKUM ISLAM - Moch. Nurcholis (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2021)
Orientalists, in their viewpoint, place the eastern-Islamic world as an opponent that must be weakened. One of their efforts is done by portraying the face of Islam and Islamic law according to their own constructed point of view. This descriptive writing describes the orientalist view of Islam and Islamic law based on authoritative references in the theme of this study. The data used comes from library data (library research). The technique of collecting data is done in documentation, while the analysis is done with content analysis techniques. The result of the study in this paper conclude three things. First, Islam is not a religion that originates from God according to the orientalist view, but it is considered a form of religious tradition that continues the Christian and Jewish religious traditions. Second, the orientalists are of the view that Islamic law is a product of thought that was systematically compiled in detail in the era of the Umayyad dynasty and the beginning of the Abbasid era. Third, the emergence of these two orientalist views is due to their limited reading toward Islam as to complement and perfect the previous religious teachings. On the other hand, orientalists have deliberately forgotten the fact that Muslims have two legacies from the Prophet Muhammad peace and blessings of Allah be upon him, namely al-Qur'an and al-Sunnah, as the basis and source in every effort to formulate Islamic law.